1998
DOI: 10.1007/s002239900459
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Polyethylene on Osteocalcin, Alkaline Phosphatase and Procollagen Secretion by Human Osteoblastic Cells

Abstract: We have studied the direct effects of polyethylene particles on osteoblastic function in primary human bone cell cultures. The cells were obtained from trabecular bone fragments of patients undergoing knee reconstructive surgery. When the cells reached confluency, they were subcultured into two flasks, one untreated (control culture) and the other treated with polyethylene particles, and incubated until confluency. Osteoblastic function was evaluated by assaying osteocalcin, alkaline phosphatase, and C-termina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 19 publications
3
17
0
Order By: Relevance
“…10C and D). Nevertheless, only a fraction of cells (approximately 40%) seeded on the polymer remained on the polymer, while the remaining of the cells migrated to the polystyrene surface in the plate [11,24]. Since the cells that migrated to the TCPS from the polymer remained healthy and indicates that the polymer and its degradation products were not significantly toxic in vitro.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…10C and D). Nevertheless, only a fraction of cells (approximately 40%) seeded on the polymer remained on the polymer, while the remaining of the cells migrated to the polystyrene surface in the plate [11,24]. Since the cells that migrated to the TCPS from the polymer remained healthy and indicates that the polymer and its degradation products were not significantly toxic in vitro.…”
Section: Resultsmentioning
confidence: 99%
“…Collagen type I is hydroxyproline-rich protein secreted in significant concentrations by BMSC cells [23,24]. Since collagen type I contains 10-15% hydroxyproline and it is the major protein synthesized by BMSC, we measured hydroxyproline contents in the culture supernatents to compare collagen synthesis in BMSC cultured on LDI-glycerol polymer or on the TCPS.…”
Section: Resultsmentioning
confidence: 99%
“…BMSCs produce copious amounts of hydroxyproline-rich type I procollagen. 25,26 To compare the synthetic characteristics of BMSCs grown on the polymer with those of BMSCs cultured on tissue culture polystyrene (TCPS), we determined the hydroxyproline content of the culture medium after a 10-day period of cell growth. As shown in Fig.…”
Section: Cell Growth On Ldi-glucose Matrix In Vitromentioning
confidence: 99%
“…16,31 The smaller the polyethylene particles, the more they inhibited growth in these cells. 16 The other study demonstrated that the polyethylene particles directly affected osteoblastic markers in human bone cells in culture -they increased the secreted markers related to mineralization and chemotaxis and decreased PICP secretion.…”
Section: Discussionmentioning
confidence: 99%
“…Previous papers from our group, as well as other authors, have analyzed the in vitro effects of particulate debris on some markers of osteoblastic phenotype and found changes related to reduced osteoblastic activity with or without increased bone resorption. [26][27][28][29][30][31] These findings implicate altered osteoblast function in the bone loss associated with prosthetic loosening, therefore, a comprehensive model of this process must account for osteoclast bone resorption, as well as the possibility that osteoblast function could also be affected.…”
Section: Introductionmentioning
confidence: 99%